Health care for people with sickle cell disease in a medium-sized Brazilian city - de Oliveira, Mário Cézar; Pires, Rosana Paula; Araújo, Lúcio Borges; de Oliveira, João Carlos; Alcântara, Tânia Machado (Open Science Journal, 2020)
The objective of the study was to evaluate the access, assistance and satisfaction of people with sickle cell disease in relation to the health care provided by the Unified Health System in the Uberlândia city, Minas Gerais, Brazil. Thirty-four people with sickle cell disease were recruited using the snowball sampling method and submitted to semi-structured interview, with collection of demographic, clinical and relationship data and satisfaction with health care. Forty-four percent were not included in the Primary Health Care network, which did not provide several procedures/actions recommended by the Ministry of Health. Ninety-four percent were unsatisfied/partially satisfied with the emergency care provided in the Integrated Care Units. The main reasons for this unsatisfied were ignorance of sickle cell disease by the health team (87.5%), delay in care (81.3%) and inadequate conduct by the health team (59.5%). In conclusion, the access and quality of care provided to people with sickle cell disease by the Primary Health Care network and the Urgency and Emergency Network need to be improved and this improvement is directly related to the training of health teams.